The updated network meta-analysis of the therapeutic efficacies of lung cancer: A systematic review and meta-analysis - Chuan-Hsin Chang; Chih-Cheng Chien; Yue-Cune Chang (Tzu Chi Medical Journal, 2025)
Objectives: Lung cancer is one of the most common malignancies worldwide. We aim to investigate the most effective treatments for advanced/nonadvanced stages of lung cancer patients. Materials and Methods: We searched electronic databases to investigate the treatment efficacies of lung cancer. The network meta-analysis was used to identify the top five most effective therapeutic strategies. A total of 157 studies were collected with a cumulative total of 164,678 participants. Results: The results showed that the best top five treatments: (1) for advanced lung cancer in response rate, were Chemo + Chemotherapy + Targeted Therapy, Cell therapy + Immunotherapy, Targeted Therapy + Radiotherapy, Chemoradiotherapy + Immunotherapy, and Chemotherapy + Chemoradiotherapy with cumulative probabilities 50.5, 49.6, 47.7, 46.0, and 45.6%; (2) for advanced lung cancer in progression-free survival (PFS) rate, were Targeted + Radiotherapy, Targeted + Others Therapy, Targeted + Targeted Therapy, Immu + Immu + Chemo Therapy, and Chemoradiotherapy with cumulative probabilities 99.5, 82.8, 44.9, 36.5, and 33.6%; (3) for nonadvanced lung cancer in response rate, were Chemoradiotherapy + Immu, Chemoradiotherapy + Targeted therapy, Chemoradiotherapy + Others, Chemotherapy + Surgery, and Radiotherapy + Others with cumulative probabilities 79.1, 74.9, 66.9, 60.4, and 54.2%; (4) for non-advanced lung cancer in PFS rate, were Chemo + Surgery, Chemoradiotherapy + Targeted, Surgery, Surgery + Radiotherapy, and Chemoradiotherapy + Others with cumulative probabilities 88.3, 86.1, 78.3, 73.1, and 50.8%. Conclusion: We present the latest and most effective therapeutic strategies for patients with advanced or nonadvanced stages of lung cancer.